SIRE: Catalyst for Improvements in Accounting and Tax Processes - Rufasto , Alexa Mundaca; Lucumí , Nancy Paola Ruiz; Rodríguez , Víctor Hugo Puican (Journal of Ecohumanism, 2024)
The Integrated Electronic Registration Systems have had a positive impact on the accounting and tax processes of SMEs. The article explored the impact of the Integrated Electronic Registration Systems| (SIRE, from the Spanish initials) on the accounting processes of SMEs in Peru, comparing it with practices in Ecuador and Colombia. For this purpose, 60 professionals participated in the study, which used a quantitative approach and the application of a survey and document analysis. The results of the study were analyzed quantitatively and qualitatively, thus examining how digitalization affects the efficiency and accuracy of accounting and tax processes. In terms of correlation results, there is a 63.10% correlation between SIRE and the accounting processes, while there is a 56% correlation between digital transformation and the accounting processes. Key lessons for policy makers and system designers were identified, emphasizing future reforms to facilitate an effective digital transition. This paper contributes to understanding how digitalization improves the economic performance and tax compliance of SMEs, providing a basis for future research and strategies aimed at integrating these companies into the digital economy.